Temporal dynamics of species associations in the parasite community of European eels, Anguilla anguilla, from a coastal lagoon - Giari L.; Ruehle B.; Fano E. A.; Castaldelli G.; Poulin R. (International Journal for Parasitology: Parasites and Wildlife, 2020)
The resilience of biological communities is of central importance in ecology, but is difficult to investigate in nature. Parasite communities in individual hosts provide good model systems, as they allow a level of replication usually not possible with free-living communities. Here, using temporal data (2005–2017) on the communities of endohelminth parasites in European eels, Anguilla anguilla, from brackish-water lagoons in Italy, we test the resilience of interspecific associations to changes in the abundance of some parasite species and the disappearance of others. While most parasite species displayed changes in abundance over time, three trematodes that were present in the early years, two of which at high abundance, completely disappeared from the parasite community by the end of the study period. Possibly other host species required for the completion of their life cycles have declined in abundance, perhaps due to environmental changes. However, despite these marked changes to the overall community, pairwise correlations in abundance among the three most common parasite species (all trematodes) were stable over time and remained mostly unaffected by what happened to other species. We explore possible reasons for these resilient species associations within a temporally unstable parasite community inhabiting a mostly stable host population.